Figurative Language in the Lyrics of Animation Film: ‘Tinker Bell and The Lost Treasure’ Soundtrack - Maisarah, Ira; Wati, Gustina (UNIB Press, 2023)
Figurative language relates to the use of words outside of their usual context and meaning to express complex ideas. Figurative language is commonly found in the work of literature including song lyrics. This research purpose is to investigate the type of figurative language presented in the Original Soundtrack of the animation Film: ‘Tinker Bell and The Lost Treasure' and the type of figurative language that is the most dominant found in the Original Soundtrack of the animation Film: 'Tinker Bell and The Lost Treasure'. The mixed method design of the research was used to analyze the data by using a document checklist as the instrument of the study. 8 song lyrics were analyzed and the result showed that the figurative languages found in the Tinker Bell and The Lost Treasure Original Soundtrack were (1) Metaphor, (2) Personification, (3) Metonymy, (4) Allegory, (5) Symbol, (6) Paradox, and (7) Hyperbole. While in the figurative language which is dominantly presented in the Original Soundtrack of Tinker Bell and The Lost Treasure is figurative language of symbol. Songwriters usually use figurative language to make the lyrics more beautiful. Analyzing figurative language presented in the song lyric is important to understand what the song lyric means behind the figurative language used.